Communication and the construction of social identity: an analysis of the relationship between communication and social identity formation (Revista Científica Interdisciplinaria Investigación y Saberes, 2023)
Communication and identity formation are key topics in sociological theory. In this study, the bibliographic method was used to identify the most relevant theories and concepts on the relationship between communication and the construction of social identity. The results suggest that this process is dynamic and develops through social interaction and communication. In the digital era, media and social networks play an important role in the construction of identity, as they influence how we perceive ourselves and how we relate to others. The authors agree that communication is fundamental to transmit common meanings and values that allow us to understand our environment and define our identity in relation to others. Currently, communication and the construction of social identity address different aspects related to the influence of digital technologies and artificial intelligence on the way in which identity is constructed and represented online.